Improved procedure for dendrimer-based mass calibration in matrix-assisted laser desorption/ionization-time-of-flight-mass spectrometry - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2016)
A procedure is described that results in a substantial increase in signal intensity and in improved accuracy of positive-ion mass calibration when using commercially available kits of monodisperse dendrimers (SpheriCal®) in matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS). The peak intensities are amplified by an admixture of 2-[(2E)-3-(4-tert-butylphenyl)-2-methylprop-2-enylidene] malononitrile (DCTB) matrix to the kits comprising of 9-nitroanthracene matrix, sodium trifluoroacetate, and four dendrimers. Boosted ion formation then permits lower laser fluence to be used and thus yields enhanced mass resolution. Further, the number of reference peaks is doubled by doping the sample preparation with cesium ions. This results in four [M+Cs]+ ion signals in addition to four [M+Na]+ ion signals provided by the standard kit. Overall, the modified procedure notably reduces the consumption of the expensive calibration standard kits, while it increases mass resolution and enables the use of an advanced calibration algorithm requiring at least six reference peaks.
Gesehen am 11.08.2020